The Effect of Variation Concentration of Simplex Syrup on the Physicochemical Stability of Nanosilver Syrup - Dian Eka Ermawati; Yavi Hanuriansyah; Nindita Clourisa Amaris Susanto; Sholichah Rochmani; Diyah Tri Utami; M. Fiqri Zulpadly; Heru Sasongko; Ulfa Afrinurfadhilah Darojati; Annisa Diyan Meitasari; Meta Kartika Untari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Inulin from Gembili has been identified as an effective bioreductor for forming nanosilver with a size of 481.4 nm, stable for 30 days when stored at 4°C. Inulin nanosilver exhibits immunomodulatory properties and has been proven safe through acute toxicity evaluation at a dose of 4 mg/kgBB. A drug delivery system needs to be developed for its use as a supplement. Syrup was chosen due to its alcohol-free nature, better taste, and ease of measuring the active substance compared to elixirs, solutions, and suspensions. Simplex syrupus, used as a syrup base, influences stability by potentially forming crystals during storage. This research aims to determine how varying concentrations of simplex syrupus affect the physicochemical properties of inulin nanosilver syrup. The study involved the biosynthesis process using Gembili's inulin, nanosilver characterization, formulation, and stability testing. Inulin nanosilver syrup was prepared with simplex syrupus concentrations of 20%, 40%, and 60%. The physicochemical stability of the syrup, including organoleptic properties, pH, and viscosity, was tested before and after storage at 4°C and 40°C over six cycles. The selected formula was evaluated for sugar reduction content and FT-IR profile. Data analysis was performed using SPSS 21.0 for Windows with One-way ANOVA and Paired T-Test. Results indicated that higher concentrations of simplex syrupus led to increased consistency, pH, and viscosity. A 60% concentration of simplex syrupus met the physicochemical stability requirements, with a medium-thick consistency, pH of 5.25±0.03, and viscosity of 92±2.6 cps. The reducing sugar content was 20.59% ±0.002, and the FT-IR profile confirmed the presence of inulin nanosilver, indicated by Ag-N groups compared to silver nitrate solution. This product has the potential to be developed as a health supplement.